The quest for economic reform and structural transformation in the Arab region - Handoussa, Heba (OFID ViennaAT, 2007)
Focuses on the characteristics of Arab countries undertaking reforms which have been handled with extreme gradualism and caution, thereby costing the region significant growth opportunities and contributing to the absence of a consistent and sustainable development path. Opines that although there may be growth, development may not necessarily occur without access to services and opportunities as well as a dignified standard of living.